Self- Realization and Society in Gandhi’s Hind Swaraj (1909) - Sharma, Madhukar (Lumbini Journal of Language and Literature, 2022)
This paper tries to explore the role of self-realization as one of the primal solutions to psycho- socio-economic and political problems facing the individual, community, nation, and the world with reference to Mahatma Gandhi’s “Hind Swaraj”. Gandhi’s philosophy appears most clearly enunciated in Hind Swaraj (1909), a book written during his days in South Africa. The study investigates the issue of why the speaker gives more priority to self-realization while criticizing modern society as a major hindrance to free individuals, community, nation, and the world. The researcher argues that the speaker in this text wants to see his human world free from all kinds of socio-economic, political, and religious problems. The research approach adopted in this paper includes the opinions, and findings drawn from different research scholars and critiques. The conclusion drawn from this study is that self-realization should be seen as the main dimension of self-connectedness, authenticity, and the ability to realize and express ourselves through our work and thoughts.